2009
DOI: 10.1002/adma.200800764
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Superparamagnetic Ferrogels for Controlled Release of Hydrophobic Drugs

Abstract: A ferrogel for magnetically controlled release of drugs is prepared by integration of superparamagnetic iron oxide nanoparticles and Pluronic F127 gels. The hydrophobic drug indomethacin is loaded in the ferrogel owing to the oil‐in‐water micellar structure. The characteristic sol–gel transition property renders the ferrogel an injectable drug carrier that will be, in principle, free from surgical implant procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
131
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 51 publications
2
131
0
2
Order By: Relevance
“…Peptides containing the arginine-glycine-aspartic acid (RGD) amino acid sequence, a ubiquitous cell-binding domain found in many extracellular matrix molecules, were covalently coupled to the alginate. Iron oxide particles with diameters ∼10 nm were embedded in the alginate, which results in a superparamagnetic gel (39). Macroporous structures with interconnected pores in the micrometer range were generated from the gels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides containing the arginine-glycine-aspartic acid (RGD) amino acid sequence, a ubiquitous cell-binding domain found in many extracellular matrix molecules, were covalently coupled to the alginate. Iron oxide particles with diameters ∼10 nm were embedded in the alginate, which results in a superparamagnetic gel (39). Macroporous structures with interconnected pores in the micrometer range were generated from the gels.…”
mentioning
confidence: 99%
“…Recent studies have shown controlled release of a number of drugs from ferrogels subject to magnetic fields (32)(33)(34)(35)(36)(37). Ferrogels have also been made biodegradable (38) and injectable (39). However, typical ferrogels for drug delivery demonstrate very limited deformation and volumetric change, and the pore sizes in most ferrogels are in the nanometer range (36), which limits transport of large molecules and cells through the gels.…”
mentioning
confidence: 99%
“…[630] However, since ferrogels have an intrinsically hydrophilic nature, most of these studies are focused only on water-soluble drug. In this matter, a pioneering study performed by Qin et al [631] addressed the problem of effective incorporation of important hydrophobic drugs in ferrogels by employing Pluronic-F127 micelles encapsulating SPIONs. In fact, in addition to proper biocompatibility, high stability, and low toxicity features, [632] Pluronic copolymers could associate into micelles via hydrophobic interactions above a certain critical concentration and temperature.…”
Section: Magnetic Drug Targetingmentioning
confidence: 99%
“…Reproduced with permission. [631] www.advancedsciencenews.com www.advhealthmat.de on magnetic tumor targeting in CT26 tumor-bearing mice (Figures 39a,b). It was shown that uptake in tumors exposed to magnetic field (TU+) is significantly higher compared to that of unexposed (TU−) (Figure 39c).…”
Section: Magnetic Drug Targetingmentioning
confidence: 99%
“…Lin, Watanabe, Kimura, Hanabusa, & Shirai, 2003;Mitsumata et al, 1999;Resendiz-Hernandez, Rodriguez-Fernandez, & GarciaCerda, 2008;Szabo, Czako-Nagy, Zrinyi, & Vertes, 2000;Zrinyi, Barsi, & Buki, 1997), and their derivative copolymers (C. L. Lin, Chiu, & Don, 2006). Also prevalent are gelatin (Saslawski, Weingarten, Benoit, & Couvreur, 1988) and copolymers of polyethylene oxide (Qin et al, 2009;Wormuth, 2001). Significantly less attention has been given to hydrophobic magnetic elastomers, which include a few instances of polydimethylsiloxane (Evans et al, 2007;Jolly, Carlson, Munoz, & Bullions, 1996;Varga, Feher, Filipcsei, & Zrinyi, 2003) and polystyrene (Timonen et al, 2010).…”
Section: Polymer Candidatesmentioning
confidence: 99%